Facebook and Martin Luther. Issue 1 (2nd November 2021) - Watts, James W.
Abstract : It is widely believed that the ease of internet publishing in the early twenty–first century has undermined respect for expertise, raising fears of interpretive anarchy in popular discourse about science, politics, and morality. The internet has increased access not only to information but also to the means of publication. The results have been intentionally and unintentionally disruptive to politics (growing demagogic nationalism) as well as to various kinds of businesses (such as newspapers). These developments, however, are not unprecedented, except perhaps in scale. They are the typical social side effects of introducing new media technologies. New media have historically fueled populist movements in religion and politics, as a review of Christian history shows. It also shows that the new media then get used to recreate methods for reasserting the interpretive authority of experts. These rival tendencies are generated by the three-dimensional nature of all written media. These social consequences are therefore intrinsic to writing's use ever since its invention five thousand years ago.